2021
DOI: 10.3748/wjg.v27.i47.8156
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter magnetic resonance imaging of liver fibrosis in a bile duct ligation mouse model

Abstract: BACKGROUND Bile duct ligation (BDL) in animals is a classical method for mimicking cholestatic fibrosis. Although different surgical techniques have been described in rats and rabbits, mouse models can be more cost-effective and reproducible for investigating cholestatic fibrosis. Magnetic resonance imaging (MRI) has made great advances for noninvasive assessment of liver fibrosis. More comprehensive liver fibrotic features of BDL on MRI are important. However, the utility of multiparameter MRI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a bile duct ligation mouse model, the T1 value was not correlated, but the T2 value, or the difference between pre-enhanced T1 and post-enhanced T1 values, was signi cantly correlated with the hepatic brosis rate [20]. Another study reported that the T1 mapping-based hepatocyte fraction method was more accurate than the reduction rate for determining the stage of liver brosis, suggesting that the calculation of hepatocyte fractions is a superior method for non-invasive liver brosis staging [21].…”
Section: Discussionmentioning
confidence: 90%
“…In a bile duct ligation mouse model, the T1 value was not correlated, but the T2 value, or the difference between pre-enhanced T1 and post-enhanced T1 values, was signi cantly correlated with the hepatic brosis rate [20]. Another study reported that the T1 mapping-based hepatocyte fraction method was more accurate than the reduction rate for determining the stage of liver brosis, suggesting that the calculation of hepatocyte fractions is a superior method for non-invasive liver brosis staging [21].…”
Section: Discussionmentioning
confidence: 90%
“…[16][17][18][19][20]66 One study that measured both was performed by using a T 1 -weighted sequence with a resolution of 0.14 Â 0.14 mm 2 and 2-mm slice thickness at 7 T. 15 The duration of the protocol was not reported. Besides, liver volume measurements in adult mice took 6 and 4 min applying a T 1 and T 2 sequence at 3 T, 67 respectively, 42 min with a 3D gradient echo technique (resolution 0.09 Â 0.117 Â 0.234 mm 3 ) at 4.7 T, 68 and furthermore, also spin and gradient echo sequences were applied for this purpose with a resolution of 0.14 Â 0.14 mm 2 at 4.7 T 69 (measurement time not reported). The comparatively long duration of our imaging protocol was attributable to our use of 20 NSA.…”
Section: Assessment Of the Mri Protocolmentioning
confidence: 99%
“…CCl 4 acts as the hepatotoxic agent used to create liver injury and fibrosis mouse models such as hepatotoxicity in humans which is marked by hepatic lobule necrosis [ 11 ]. Bile duct ligation (BDL) is a method that induces cholestasis and creates a model of liver fibrosis [ 34 ].…”
Section: Livermentioning
confidence: 99%